PELAKSANAAN PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA YANG DIBUAT DENGAN AKTA DIBAWAH TANGAN PADA BANK DANAMON SIMPAN PINJAM CABANG PRAWIROTAMAN JOGJAKARTA - , Muhamad Sidiq ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims to : (1) to know why Bank Danamon Simpan Pinjam Branch Prawirotaman Yogyakarta do this fiduciary agreement using a agreement underhand (2) to know the actions of Bank Danamon Simpan pinjam branch Prawirotaman Yogyakarta debtors that do not pay the installments according the agreement. The research is a judicial empirical research, which explains about some provisions in the prevailing law and regulations in relation to the implementations in practice. The research data consists of secondary data obtained from library reseacrh and primary data obtained from field research. The collected data is then analyzed qualitatively and presented descriptively. The result show that : (1) factor causes Bank Danamon Simpan Pinjam branch Prawirotaman Yogyakarta do this fiduciary agreement using a agreement underhand is to help customers reduce the cost, business competition, a program specific policies, and a small loan and the loan period is relatively short. (2) the actions of Bank Danamon Simpan Pinjam Branch Prawirotaman Yogyakarta to settle non performing financing with fiduciary guarantee made underhand use is by restructuring, giving warning to the debtor to immediately pay the installments, or by way of urging the debtor to sell collateral.